2018
DOI: 10.1089/jpm.2018.0103
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between Goals of Care and Treatment Decisions for Persons with Dementia

Abstract: Most families chose comfort as the primary GOC. Further research is needed to translate this preference into comfort-focused treatment plans for late-stage dementia. Clinicaltrials.gov : NCT01565642 (3/26/12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Our results confirm prior research describing advance directives among NH residents with advanced dementia, 16,35,36 but further that work by examining the pattern of those directives in the context of care preferences as stated by their proxies. As in earlier research, we found that most residents had DNR orders, whereas directives to withhold hospital transfers, tube-feeding, and IV hydration were less common, and directives to withhold antibiotics were particularly low.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results confirm prior research describing advance directives among NH residents with advanced dementia, 16,35,36 but further that work by examining the pattern of those directives in the context of care preferences as stated by their proxies. As in earlier research, we found that most residents had DNR orders, whereas directives to withhold hospital transfers, tube-feeding, and IV hydration were less common, and directives to withhold antibiotics were particularly low.…”
Section: Discussionsupporting
confidence: 88%
“…As in earlier research, we found that most residents had DNR orders, whereas directives to withhold hospital transfers, tube-feeding, and IV hydration were less common, and directives to withhold antibiotics were particularly low. 16,35,36 Advance directive ascertainment requires two conditions; first, clinicians must discuss a particular treatment with proxies, and second, proxies must make a deliberate decision to withhold that treatment. Not surprisingly, DNR was the most prevalent directive, as it is both widely addressed in ACP discussions, 25 and a relatively straightforward decision as resuscitation is very aggressive and not beneficial for residents with life-limiting disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because improving staff level outcomes is a necessary precondition before being able to change outcomes for residents and families, we feel this is an important first step in the effectiveness assessment of ACP+. Follow-up funding will enable us to also assessretrospectivelywhether the ACP+ programme had an effect on care concordance at the end of life, based on chart reviews and family interviews of nursing home residents who died during trial period [41,42], and we will include residents and their families from intervention nursing homes in the process evaluation to evaluate their experiences. We do stipulate that this rationale underlying the study's aim, generates an additional study limitation, given that changes in staff knowledge/self-efficacy may lead to changes in both behaviour as well resident outcomes.…”
Section: Discussionmentioning
confidence: 99%